Coating of steel wires with Zn-Al-Mg alloy and investigation of coating characterization - Ayman, Teslime; Orhan, Ayhan (Gazi Univ, Fac Engineering Architecture, 2023)
Purpose: To increase the corrosion resistance of steel wire with Zn-Al-Mg alloy coating and characterization of it. Theory and Methods: In this study; research and testing have been carried out for the development of Zn-Al-Mg alloys which will exhibit high corrosion resistance even under severe environmental conditions and for the prolongation of the limited corrosion life of steel wires by coating them on cold drawn steel wire surfaces with no problems. Microstructure analysis, salt spray test and potentiostat analysis were carried out for Zn, Zn-Al and Zn-Al-Mg alloy coated specimens to determine the coating quality, winding test was carried out for plastic formability and the results were compared with each other. Results: Zn-Al-Mg alloy coating layers are homogeneous and grain density ratios on the surface are denser than Zn-5% Al alloy coatings and thinner grain sizes are observed. Compared to Zn-% 5Al Alloy Coating The oxygen diffusion from coating to steel surface is prevented thanks to more dense grain distribution of Zn-% 5Al-% 1Mg alloy coating. In salt spray test, while the Zn %100 coating has the lowest corrosion resistance, Zn-% 5Al-% 1Mg coating has the highest corrosion resistance with 3000 hours. The open circuit potential value of the 100% Zn containing coating sample after the potentiostat test has the highest corrosion rate compared to the other samples. When the obtained corrosion rate values are compared, the lowest corrosion rate, is the highest corrosion resistance value, belongs to the coating sample containing Zn -5Al -1% Mg. No cracking in the coating layer was observed in any of the samples after the winding test in order to determine suitability of the coating to plastic shape. Conclusion: The limited corrosion life of steel wires can be extended with galvanized alloy baths which are made with different element additives as a result of research and trial works. In this context, Mg metal significantly increases the corrosion resistance compared to conventional coatings.
Keywords: Corrosion; Steel Wire; Zn-Al-Mg Coating